The non-local effects of 7-week foot sole static stretching and foam rolling training on shoulder extension range of motion - Konrad, Andreas; Reiner, Marina; Manieu, Josefina; Fischer, Josef; Schöpflin, Adrian; Tilp, Markus; Behm, David G. (Frontiers in Sports and Active Living, 2024)
Static stretching and foam rolling can increase the range of motion (ROM) of a joint acutely as well as chronically. Although studies have reported ROM increases of a non-stretched heterologous muscle (non-local) following an acute static stretching or foam rolling session, these effects have not been studied for long-term training interventions. Therefore, the purpose of this study was to investigate the effects of a comprehensive 7-week static stretching and foam rolling training program of the foot sole on shoulder extension ROM. A total of 33 healthy, physically active participants (20 male) were assigned to either the intervention (n = 19) or control (n = 14) group. The intervention group performed a 7-week combined static stretching and foam rolling intervention comprising three sessions a week, including three exercises of the foot sole for 5 min each. Before and after the intervention period, the shoulder extension ROM was tested with three-dimensional (3D) motion caption. The level of significance for all statistical analyses was set to ρ ≤ 0.05. There was no significant time (p = 0.70, F1, 31 = 0.157; η2 = 0.005) or time×group effect (p = 0.38, F1, 31 = 0.785; η2 = 0.025) in shoulder extension ROM, indicating no ROM changes in the intervention or the control group. Although previous studies on the acute effects of stretching and foam rolling reported non-local increases in ROM in heterologous muscles, this study could show that such effects do not occur after chronic SS and foam rolling training for 7 weeks. Consequently, if the goal is to chronically increase the ROM of a specific joint, it is recommended to directly treat the muscles of interest.